2006
DOI: 10.1111/j.1440-1754.2006.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Serious injury is associated with suboptimal restraint use in child motor vehicle occupants

Abstract: A total of 82% of child occupants aged 2-8 years involved in crashes were suboptimally restrained. All children who sustained serious injuries were suboptimally restrained. There is a need to encourage correct use of the most appropriate restraint for child motor vehicle occupants in order to reduce the number and severity of injuries in these road users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
52
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 12 publications
3
52
2
1
Order By: Relevance
“…This finding is inconsistent with previous studies that reported increased likelihood and severity of injury among children who were inappropriately restrained (Brown, McCaskill, Henderson, & Bliston, 2006;Lutz et al, 2003;Durbin, Kallan, & Winston, 2001). This apparent inconsistency may be due to differences in study design and sample size.…”
Section: Discussioncontrasting
confidence: 76%
“…This finding is inconsistent with previous studies that reported increased likelihood and severity of injury among children who were inappropriately restrained (Brown, McCaskill, Henderson, & Bliston, 2006;Lutz et al, 2003;Durbin, Kallan, & Winston, 2001). This apparent inconsistency may be due to differences in study design and sample size.…”
Section: Discussioncontrasting
confidence: 76%
“…Durbin et al (2003) reported that, in 4-to 7-year-old children, the use of booster seats reduced the risk of head and brain injuries, all internal organ injuries, spinal cord injuries, and extremity fractures by 59 percent compared to seat belts. An Australian case-control study investigated the injuries sustained by children aged 2 to 8 years in motor vehicle crashes (Brown et al 2005(Brown et al , 2006. Though no serious or fatal injuries were observed among optimally restrained children, 30 percent of suboptimally restrained children sustained serious or fatal injuries.…”
Section: Introductionmentioning
confidence: 99%
“…3 In 2006, Brown et al reported sub-optimal child restraint practices were widespread among restrained crash-involved child occupants aged 2-8 years in New South Wales (NSW), and this was associated with a higher risk of serious injury. 4 There is considerable scope to prevent these injuries by encouraging best practice child car restraint use.…”
mentioning
confidence: 99%